Pericapsular nerve group (PENG) block versus supra-inguinal fascia iliaca (SIFI) block for functional outcome in patients undergoing hip surgeries – A randomised controlled study - Tanusha Saini; Meenakshi Aggarwal; Udeyana Singh; Mirley Rupinder Singh (Indian Journal of Anaesthesia)
Background and Aims: In hip surgeries, the pericapsular nerve group (PENG) block and supra-inguinal fascia iliaca (SIFI) block are commonly employed perioperative regional analgesia techniques. This study aimed to compare functional outcomes regarding quadriceps muscle strength and weight-bearing capacity between PENG and SIFI blocks after hip surgery. Methods: In this single-centre, double-blinded, randomised trial, 60 patients undergoing hip surgeries under subarachnoid block were randomised into either Group P (PENG block) or Group S (SIFI block). Blocks were administered under ultrasound guidance with 30 mL of 0.2% ropivacaine and 4 mg dexamethasone. Functional mobility was assessed 24 and 48 h postoperatively by measuring quadriceps strength and maximum weight-bearing capacity. Analgesic efficacy was also evaluated by comparing visual analogue score (VAS) scores at 24 h, total opioid consumption over 24 h, and duration of analgesia. Statistical analysis included Student’s t-test, Chi-square, and Z-test as appropriate, with statistical significance set at P < 0.05. Results: Group P demonstrated significantly higher quadriceps-muscle strength at 24 h (P = 0.025) and 48 h (P = 0.002) post surgery. More patients in Group P achieved superior weight-bearing grades at 24 h (P = 0.002) post surgery compared to Group S. VAS scores were significantly lower in Group P at 24 h post surgery (P = 0.006). Group P also showed a prolonged duration of analgesia (P = 0.019) and lower mean opioid consumption (P = 0.001) compared to Group S. Conclusion: The PENG block may be superior to the SIFI block in terms of functional outcomes with better quadriceps strength, enhanced weight-bearing, and provision of more effective postoperative analgesia in hip surgery patients.